2021
DOI: 10.1155/2021/2225426
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl alcohol) Hydrogels: The Old and New Functional Materials

Abstract: Hydrogels have three-dimensional network structures, high water content, good flexibility, biocompatibility, and stimulation response, which have provided a unique role in many fields such as industry, agriculture, and medical treatment. Poly(vinyl alcohol) PVA hydrogel is one of the oldest composite hydrogels. It has been extensively explored due to its chemical stability, nontoxic, good biocompatibility, biological aging resistance, high water-absorbing capacity, and easy processing. PVA-based hydrogels have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 146 publications
(187 reference statements)
1
54
1
Order By: Relevance
“…In addition to mechanical strength, the crosslinking degree affects hydrogel adhesion simultaneously. For PVA hydrogels prepared by the F-T cycle, on the one hand, most of the hydroxyl groups on PVA formed hydrogen bonds used for crosslinking during the F-T process, which resulted in the lack of free hydroxyl groups used for adhesion [ 7 , 27 ]. On the other hand, the increase in the crosslinking degree of the PVA hydrogels limited the accessibility of hydroxyl groups due to the decrease in segment mobility.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to mechanical strength, the crosslinking degree affects hydrogel adhesion simultaneously. For PVA hydrogels prepared by the F-T cycle, on the one hand, most of the hydroxyl groups on PVA formed hydrogen bonds used for crosslinking during the F-T process, which resulted in the lack of free hydroxyl groups used for adhesion [ 7 , 27 ]. On the other hand, the increase in the crosslinking degree of the PVA hydrogels limited the accessibility of hydroxyl groups due to the decrease in segment mobility.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it is also desired for tissue engineering that such materials intrinsically show improved mechanical properties (such as hardness and elasticity) and structure (such as porosity and density) in order to be compatible with embedded tissues. So far, the development of multifunctional hydrogels to meet complex biological conditions in vivo and achieve the adequate synergy with live organisms remains a current challenge [ 34 ]. Based on the concept, among the different polymers used to date, PVA deserves especial attention because it could be an excellent polymer that has several beneficial effects and is easy to form complex microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels prepared from a single material are widely used in biological tissue engineering [ 2 ]. However, in other application fields, such as contact lenses [ 3 ], wound dressings [ 4 ], slow drug release [ 5 ], tissue scaffolds [ 6 ], and drug delivery carriers [ 7 ], low strength and toughness limit the development of hydrogels. Studies have shown that the common mechanical properties of hydrogels are as follows.…”
Section: Introductionmentioning
confidence: 99%